2020
DOI: 10.1177/0300060520937623
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis complicated with multiple organ dysfunction syndrome after breast augmentation with fat from the waist and lower extremities: a case report

Abstract: Necrotizing fasciitis (NF) is a rapidly progressing soft tissue infection with a mortality rate as high as 30% to 50%. However, the incidence rate of NF after liposuction is extremely low. In the current case report, we describe a woman with NF who developed multiple organ dysfunction syndrome (MODS) after fat acquisition. The aim of this paper is to summarize the management of these patients. After debridement and drainage, correction of multiple organ failure, and plastic surgery, the patient’s organ and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The other patient (reported by Sharma) had NF of the abdominal wall after liposuction for augmentation mammoplasty but no breast complications [131]. In preparation for bilateral breast augmentation with fat injection, another patient developed NF of the bilateral thighs and waist where liposuction was performed [132]. These last two cases demonstrated that liposuction to obtain body fat for breast augmentation can be complicated by either NF or NSTI.…”
Section: Discussionmentioning
confidence: 92%
“…The other patient (reported by Sharma) had NF of the abdominal wall after liposuction for augmentation mammoplasty but no breast complications [131]. In preparation for bilateral breast augmentation with fat injection, another patient developed NF of the bilateral thighs and waist where liposuction was performed [132]. These last two cases demonstrated that liposuction to obtain body fat for breast augmentation can be complicated by either NF or NSTI.…”
Section: Discussionmentioning
confidence: 92%
“…The complication rate for this procedure is estimated at 5%, and the occurrence of infections, such as NF, is considered rare. Its incidence is reported as 0.7% of cases when multiple procedures are performed along with liposuction [2,3]. In our case, we report a 35-year-old lady who developed NF following a liposuction procedure.…”
Section: Introductionmentioning
confidence: 80%
“…Management options include surgical excision of the affected tissues, supportive care, and combined antibiotic therapy. Nevertheless, mortality rates remain high especially after surgical interventions as it may reach up to 30-50% [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…NF can be idiopathic or secondary (after trauma, chronic wounds, or skin abrasions). 4,5 Diagnosis can often be challenging and is primarily diagnosed based on clinical presentation. NF has a mortality rate of 8.7%-76%, underscoring the need for timely and accurate diagnosis and prompt medical and surgical treatment.…”
Section: Introductionmentioning
confidence: 99%